LANDMARK SEBAGAI STRATEGI KREATIF IKLAN TEH BOTOL SOSRO VERSI “UNIKNYA NEGERI” PRODUKSI 25 FRAMES - Kunti, Dewi; Murfianti, Fitri (CITRAWIRA : Journal of Advertising and Visual Communication, 2020)
Competition to attract consumer attention through television advertising is getting tighter. Ad designers are required to develop creative strategies to get consumers' attention. This research examines landmarks as a creative strategy for the advertisement of Teh Botol Sosro, the Unique Version of the Country which was produced by 25 Frames to attract the attention of television audiences. Observations and documentation, as well as in-depth interviews with the Art Director and the Director of Photography were carried out to obtain valid data from the ad designers. By applying the SWOT concept and Madjadikara's television ad design process, it can be understood that the creative process of designing a teh botol sosro advertisement. The results showed that the big idea of using landmarks was obtained from the client brief process which was followed up in the creative brief process to get a more mature concept to fit the tagline "Whatever ... Drinking Teh Botol Sosro". The Ad Designer tries to remind the audience and inform consumers about the Teh Botol Sosro products through the city landmarks and the diversity of Indonesia contained in the advertisement.